2022
DOI: 10.3390/ijpb14010002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fruit Quality Traits and Biochemical Properties in Different Myanmar Mango Cultivars during Ripening Stages

Abstract: Here, we characterized the changes in fruit quality and biochemical parameters in four Myanmar mango cultivars from ripening stage 1 to 4 at ambient temperature. Total soluble solids, total sugars, and reducing and non-reducing sugar content increased, whereas titratable acidity decreased with increasing storage time in all cultivars. ‘Sein Ta Lone’ showed the highest consumer acceptability, with maximum sensory quality scores owing to its unique characteristics. ‘Hin Thar’ and ‘Ma Chit Su’ also had better qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The sugar/acid ratio of mangoes treated with ClO 2 (g) reached 44.66 on day 4, which was close to the sugar/acid ratio of fully ripe Kaew mango of about 50 [45]. Sugar/acid ratios ranging from 23 to 50 were considered high-quality mango fruits [46], which indicated that ClO 2 (g) may improve the taste of mango. Consistently, the sensory properties of the ClO 2 (g)-treated mangoes were superior to those of ethephon-treated and the control-group mangoes, especially the sweetness was more prominent.…”
Section: Discussionsupporting
confidence: 60%
“…The sugar/acid ratio of mangoes treated with ClO 2 (g) reached 44.66 on day 4, which was close to the sugar/acid ratio of fully ripe Kaew mango of about 50 [45]. Sugar/acid ratios ranging from 23 to 50 were considered high-quality mango fruits [46], which indicated that ClO 2 (g) may improve the taste of mango. Consistently, the sensory properties of the ClO 2 (g)-treated mangoes were superior to those of ethephon-treated and the control-group mangoes, especially the sweetness was more prominent.…”
Section: Discussionsupporting
confidence: 60%
“…6,7 Generally, C 2 H 4 production and respiration occur within the fruit during ripening and affect a series of metabolic activities, such as hydrolysis of starch into sugar, leading to an increase in total soluble solid (TSS) contents and a decrease in acidity, changes in structural polysaccharides leading to flesh softening, chlorophyll degradation and carotenoid biosynthesis, changes in fruit color, and biosynthesis of volatile compounds. 8,9 Moreover, the storage of mangoes is recommended at temperatures of 13 to 15 °C and % relative humidity (% RH) of 85 to 95% to delay fruit physiological deterioration, maintain quality, and prolong postharvest life. 10 Velasquez et al (2023) exhibited that mango fruits shipped at low temperatures (8 °C) have poor consumer acceptance because of low dry matter, chilling injury (CI) disorders, and other storage disorders, resulting in grayish, scaldlike skin discoloration, electrical spotting, skin pitting, loss of flesh color, and flesh browning.…”
Section: Introductionmentioning
confidence: 99%
“…Mango has unique characteristics, such as a favorable flavor and aroma, high levels of antioxidants, as well as being a rich source of the nutrients required for a healthy life and reduced risk of fatal diseases. , Mango is classified as a climacteric fruit, which can generate ethylene (C 2 H 4 ) by itself. It involves a sequence of biological, physiological, and structural controlled changes that cause color, flavor, texture, and taste alterations. , Generally, C 2 H 4 production and respiration occur within the fruit during ripening and affect a series of metabolic activities, such as hydrolysis of starch into sugar, leading to an increase in total soluble solid (TSS) contents and a decrease in acidity, changes in structural polysaccharides leading to flesh softening, chlorophyll degradation and carotenoid biosynthesis, changes in fruit color, and biosynthesis of volatile compounds. , …”
Section: Introductionmentioning
confidence: 99%